PERTUKARAN OTOMATIS INFORMASI: KAJIAN PENDAHULUAN: Array - Lillyana Mulya; Lastria Nurtanzila (Arsip Nasional Republik Indonesia, 2018)
Automatic Exchange of Information (AEoI), popularly known soon after Panama Papers took place, shows up as one among many solutions to overcome tax fraud. Nowadays studying AEoI limits itself on economic and political aspects. The article suggests that the study should discuss exchange object i.e data among others that are considered to be digital records and their problems to be. Literature study is implemented to understand its challenge and response in the developing countries, and digital records. The results are digital records of AEoI as supporting records influencing access policy, its relations with other records and its usefullness as evidence or tax information source.